FRI0649 PREVALENCE OF ANCA AND ANA IN PATIENTS WITH PULMONARY TUBERCULOSIS. (June 2019) - AMAN, SHARMA; Chander, Yogesh; Rathi, Manish; Naidu, Gsrsnk; Jha, Saket; Minz, Ranjana; Jain, Sanjay; Behera, Digambar
Abstract : Background: Tuberculosis is known to have diverse clinical presentations, some of which may mimic systemic autoimmune diseases like ANCA associated vasculitis and systemic lupus erythematous (SLE) 1 . Considering the paucity of specific biomarkers in rheumatologic practices, caution needs to be applied while interpreting ANA and ANCA results, especially in TB endemic areas. Previous studies on prevalence of autoantibodies in tuberculosis have shown contrasting results 2, 3, 4 . Objectives: To study the prevalence of ANCA subtypes and ANA in patients with bacteriologically confirmed pulmonary tuberculosis. Methods: Patients with bacteriologically confirmed pulmonary tuberculosis were screened for recruitment. Anti-PR3, anti-MPO, anti-lactoferrin and anti-elastase ANCA subtypes were tested using enzyme-linked immunosorbent assay (ELISA). ANA was done by Indirect immunofluorescence (IIF) using Hep 2 cell lines. Patients who were positive for ANA were tested for presence for various extractable nuclear antigens using line immunoassay. Results: Eighty nine patient were recruited in the study. Median age was 28 (range 20 – 46) years. The bacteriological confirmation was done via sputum examination in 81 (79 smear and 2 Gene Xpert) patients and bronchoalveolar lavage (BAL) fluid in 8 patients (5 smear and Gene Xpert). Out of 89, 62 patients were treatment naïve for pulmonary TB. The clinical features were fever (70%), Cough (99%), expectoration (99%), dyspnea(25%), hemoptysis(25%) and chest pain(13.5%), . The radiological features were consolidation (61%), reticulonodular opacities (50%), cavity (44%), bronchiectasis (6%) and pleural effusion (8%).Among ANCA subtypes, anti-elastase was the most common and was positive in 86 (96.62%) patients, followed by anti-PR3 seen in 7 (7.8%) patients. No sera were found positive for anti-MPO and anti-lactoferrin antibodies. Six (6.7%) patients had positive ANA (IIF).Line immunoassay in these patients was positive for SS-A/Ro-52 and U1-RNP in one patient each. Conclusion: Anti PR3 ANCA positivity can be detected in patients with pulmonary tuberculosis and should be interpreted with caution in tuberculosis endemic areas. Anti-elastase ANCA was detected in majority of these patients and its role in differentiating tuberculosis from ANCA associated vasculitis needs further exploration. References: [1] Al-Hadad I, Taha O. TB, or not TB: That is the question. Respir Med CME. 2010;3:192–4. [2] Lima I, Oliveira RC, Cabral MS, Atta A, Marchi S, Reis E, et al. Anti-PR3 and anti-MPO antibodies are not present in sera of patients with pulmonary tuberculosis. Rheumatol Int. 2014;34:1231–4 [3] Huan G, Yang G, Xiao-yu Q, Jiancheng X, Yan-qing S, Huan G, et al. Antineutrophil cytoplasmic antibodies in Chinese patients with tuberculosis. Rev Soc Bras Med Trop. 2018;51:475–8. [4] Elkayam O, Caspi D, Lidgi M, Segal R. Auto-antibody profiles in patients with active pulmonary tuberculosis. Int J Tuberc Lung Dis. 2007;11:306–10 Disclosure of Interests: None declared